INVESTIGATING EFFECT OF NURSING INTERVENTIONS, BASED ON WELLS SCORE RESULTS, ON THE INCIDENCE OF DEEP VEIN THROMBOSIS IN PATIENTS ADMITTED TO THE INTENSIVE CARE UNIT - Habibi Moghadam, Morteza; Asadizaker, Marzieh; Jahani, Simin; Maraghi, Elham; Saadatifar, Hakimeh; Naanaei, Farhad (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: Venous thromboembolism, including deep vein thrombosis (DVT) and pulmonary embolism (PE), is a common complaint in critically ill patients. Therefore, the present study was conducted to determine the effect of nursing interventions, based on the Wells results, on the incidence of DVT in intensive care unit (ICU) patients. Methods: The present clinical trial was conducted on 72 ICU patients without DVT and PE who met the inclusion criteria according to Wells score in Dr. Ganjavian Hospital, Dezful in 2012. The participants were investigated and randomly divided into intervention (n=36) and control groups (n=36). The intervention group received preventive nursing measures based on the risk level determined by the Wells score, and routine therapeutic interventions were performed for the control group. Then, patients were evaluated using Wells score, D-dimer testing, and Doppler sonography on the 1st, 5th, and 10th days. Data were finally coded and entered into SPSS version 23. Data analysis was performed using Chi-square, Fisher's exact, and Mannâ€“Whitney U tests. Results: The incidence of DVT in both groups showed that 2 patients of the control group who were identified to be at risk using the Wells score were diagnosed with DVT while none of the patients of the intervention group experienced DVT. The present study showed that 22.2% of the patients of the control group suffered from non-pitting edema, which was significantly different from the intervention group (p=0.005). Conclusion: The results of the present study showed that using the Wells score for early identification of the at-risk patients and nursing interventions based on this score's results is helpful in the prevention of DVT. Appropriate nursing interventions were also effective in reducing the incidence of non-pitting edema in the lower extremities.